An assessment of public participation in South African energy infrastructure projects - Dlamini, Nthuseng (My University, 2021)
Public protests often hamper infrastructure projects, normally transpiring during project execution. Public protests profoundly influence infrastructure project execution. This study aims to assess the effectiveness of public participation in infrastructure energy projects in South Africa. The study applied mixed method approach, involving quantitative and qualitative techniques. Data were collected through two self-designed questionnaires for quantitative data analysis (43 Eskom project stakeholders and 43 external stakeholders), whilst a telephone interview was conducted on eight (8) participants. Results were analysed using a sequential explanatory mixed method design. Data collected was analysed through descriptive and inferential statistics. Correlation analysis was also applied to determine the level of association between public protest and public participation. The results identify adequate evidence to conclude that public participation in infrastructure projects’ effectiveness within the power utility holds a strong correlation of 91%. Results indicate that public protest is caused by many factors such as, dissatisfaction concerning the project; raising concerns; a lack of service delivery; a lack of communication; and project disadvantage to the community. The results denote inadequate evidence to conclude the association of public protest and public participation (p-value = 0, 23). The results further identify a strong correlation of 83% between public protests and public participation; 100% public participation is indicated to influence the community. These observations confirm adequate evidence to identify public participation in the community as a positive influence on the project; (p-value = 0, 00024). From the qualitative analysis, the study establishes the following themes, structuring public protests: Inadequate communication and a lack of trust; meeting regulations; a lack of understanding; a lack of respect; a need for collaboration and awareness; and training. Literature supporting these findings is presented in detail in this report. The study recommends proper processes and clear communication, instigating suitable and effective public participation to prevent public protest
A research report submitted to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Building, 2021